Implementation of Humanistic Theory Concepts in Islamic Religious Education - Dewi Wulandari; M Shohibul Mafariech (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to analyze the application of humanistic theory in Islamic Religious Education (PAI) learning and its impact on the learning process and students' character development. Humanistic theory, which emphasizes individual potential and a holistic approach, is applied to create a learning environment that supports students' physical, emotional, social, and spiritual needs. This research uses a qualitative method with a literature approach to review various literature related to the implementation of humanistic theory. The results show that this approach can increase students' intrinsic motivation, encourage more personalized learning, and strengthen their understanding of Islamic values. By making students the center of learning and paying attention to their individual needs, this theory succeeds in creating a more effective and meaningful learning process. The conclusion of this study is that the application of humanistic theory in Islamic Religious Education makes a significant contribution to building religious, independent, and competitive student characters while improving the overall quality of learning. This research also provides prospects for development, especially in the integration of humanistic theory with educational technology to expand its application in various learning contexts.